Nanoimaging: photophysical and pharmaceutical characterization of poly-lactide-co-glycolide nanoparticles engineered with quantum dots. (24th November 2015) - Pederzoli, F; Ruozi, B; Pracucci, E; Signore, G; Zapparoli, Mauro; Forni, F; Vandelli, M A; Ratto, G; Tosi, G
Abstract: Quantum dots (QDs) and polymeric nanoparticles (NPs) are considered good binomials for the development of multifunctional nanomedicines for multimodal imaging. Fluorescent imaging of QDs can monitor the behavior of QD-labeled NPs in both cells and animals with high temporal and spatial resolutions. The comprehension of polymer interaction with the metallic QD surface must be considered to achieve a complete chemicophysical characterization of these systems and to describe the QD optical properties to be used for their unequivocal identification in the tissue. In this study, by comparing two different synthetic procedures to obtain polymeric nanoparticles labeled with QDs, we investigated whether their optical properties may change according to the formulation methods, as a consequence of the different polymeric environments. Atomic force microscopy, transmission electron microscopy, confocal and fluorescence lifetime imaging microscopy characterization demonstrated that NPs modified with QDs after the formulation process (post-NPs-QDs) conserved the photophysical features of the QD probe. In contrast, by using a polymer modified with QDs to formulate NPs (pre-NPs-QDs), a significant quenching of QD fluorescence and a blueshift in its emission spectra were observed. Our results suggest that the packaging of QDs into the polymeric matrix causes a modification of the QD optical properties: these effects must be characterized in depth and carefully considered when developing nanosystems for imaging and biological applications.